UPAYA LOBBY HIMPUNAN MAHASIWA ISLAM KEPADA PRESIDEN SOEKARNO PADA TAHUN 1965 - Wiwid Ferdiawan; M Basri; Syaiful M (FKIP UNIVERSITAS LAMPUNG, 2015)
Formulation of the problem in this research was what were the underlying factors of Islamic Students Association (HMI) made lobbying effort to the President on the dissolution of PKI in 1965. The aimed of this research was to determine the underlying factors of Islamic Students Association (HMI) made lobbying efforts to the President in the dissolution of PKI in 1965. Data collection techniques used were through literature and documentation techniques. The method used was historical method. The data analysis technique used in this research was qualitative techniques. The result showed that the factors that affected lobbying efforts of HMI to President Soekarno influenced by internal and external factors of organization. Internal factors of HMI that affected lobbying efforts against President Sukarno namely; the doctrine of HMI Struggle, the Plenary Meeting of PB HMI and the role of HMI Senior Prominent in the cabinet. The external factors namely; The support of Army leaders to HMI, attitude of the President to the PKI and PKI efforts to disperse the HMI.Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui Faktor-faktor yang melatarbelakangi Himpunan Mahasiswa Islam (HMI) melakukan upaya lobby kepada Presiden Soekarno dalam pembubaran PKI pada tahun 1965. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah melalui teknik kepustakaan dan dokumentasi. Metode yang digunakan dalam penelitian ini adalah metode historis. Berdasarkan hasil pengumpulan data, faktor-faktor yang mempengaruhi upaya lobby HMI kepada Presiden Soekarno dipengaruhi oleh faktor internal organisasi serta faktor eksternal. Faktor Internal HMI yang mempengaruhi upaya lobby terhadap Presiden Soekarno yakni; Doktrin Perjuangan HMI, Rapat Pleno PB HMI, dan Peran Tokoh Senior HMI dalam kabinet. Sedangkan faktor eksternal yakni; Dukungan tokoh petinggi Angkatan Darat (AD) kepada HMI, Sikap Presiden Soekarno terhadap PKI, dan upaya-upaya PKI untuk membubarkan HMI.Kata kunci : faktor-faktor, HMI, presiden soekarno